Ecological view at uyun layla in Saudi Arabia - AI-Ghanem, Wafaa Mohammed (2011)
This study deals with the change in the biodiversity in uyun Layla lakes during the last 30 years. The study revealed that the aquatic habitat has been altered to terrestrial dry habitat with complete alteration in the type of vegetation covering this area. The vegetation was scanty, poor halophytic species. Only
Includes references.
Summary in Arabic.
1
Keywords: Lake ecology; Biodiversity; Vegetation and climate; Desertification